Metals and Minerals in Pharmacy: Current Trends, Biomedical Applications, and Future Innovations - Tushal Kyada; Monika Kyada (International Journal of Minerals, 2025)
Metals and minerals have played important roles in medicine for centuries, ranging from the use of simple mineral powders in traditional therapies to the development of modern metal-based drugs and nanomaterials. In recent years, advancements in material science, nanotechnology and pharmaceutical engineering have expanded the biomedical relevance of inorganic materials far beyond their conventional use as excipients. This review highlights the growing integration of metallic and mineral systems into pharmaceutical formulations, therapeutic agents, imaging platforms, antimicrobial coatings and targeted drug delivery technologies. The discussion covers essential metals, noble metal nanoparticles, clay minerals, silica-based carriers, calcium phosphates, and metal–organic frameworks, with emphasis on their physicochemical properties, biological interactions and mechanisms of action. Special attention is given to toxicity considerations, regulatory requirements and long-term biocompatibility challenges. Recent trends such as green synthesis routes, AI-assisted material selection, multifunctional nanocarriers and emerging clinical applications are thoroughly analyzed. The review concludes by identifying promising future directions, including intelligent inorganic biomaterials, personalized metallodrugs and sustainable sourcing of pharmaceutical-grade minerals. Overall, metals and minerals continue to offer broad opportunities for innovative and impactful applications in pharmacy and biomedical science
Keywords: Metal-based therapeutics; Mineral excipients; Nanomedicine; biocompatibility; biomedical applications; drug delivery; metal nanoparticles